, and
. This gives a remainder of
![(x^3+4x^2+x-6)-(x^3-x^2)=5x^2+x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hssea005p4szot96x6poq3qji58pale4zb.png)
, and
. This gives a new remainder of
![(5x^2+x-6)-(5x^2-5x)=6x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w0dhozkqynqejztd0vxagpundu0x2mk0ip.png)
, and
. This gives a new remainder of
![(6x-6)-(6x-6)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n1j7igxqo70ny4u3i4dc17ujqj7blswf35.png)
and so there is no remainder.
###
Quicker method: Use the polynomial remainder theorem, which says the remainder upon dividing a polynomial
by
is
. Here we have
![p(x)=x^3+4x^2+x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2xp6wgwhk2bx7wv0bt83vdyq5bbfw7wj1z.png)
![c=1\implies p(c)=1+4+1-6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/b6u8psnx3w9hdhd8ml5ymdpjo0uiq4ocsl.png)